Application of marketing tools in establishing loyalty in customers of PEKAO S.A. BANK 1st Branch in Rzeszów - Wiesław Szopiński (Polityki Europejskie, Finanse i Marketing)
Nowadays, in the dynamically developing market environment, at the time of great competition in the financial services market, gaining success by a bank is becoming more and more difficult. Financial institutions undertake greater and greater actions which may be the key to creating position of the bank among its competition. They permanently modify the existing and implement new solutions of a marketing character. They develop a proper strategy which might be helpful not only in establishing but also maintaining permanent dialogue with the customer. One of the main aims of each marketing strategy is establishing and creating loyalty attitudes among customers. Its success requires application of a proper range of marketing instruments. Pekao S.A. Bank, 1st Branch in Rzeszow, has had a long tradition relying on high quality of offered services as well as attractive services for local customers. The conducted empirical studies allowed to identify marketing tools and manner of its use which would determine a proper condition of services at the Bank, in comparison to the competition. Research results allow to claim that one of the most significant advantages of the analysed entity are loyal, long-lasting customers.